“La Prueba no solicitada oportunamente y aceptada por el juez deja en la indefensión a la otra parte - Calva Amaya, Yuli Vitalia (2018)
This research work is entitled "The test not timely requested and accepted by the judge leaves the other party helpless," arose from the analysis made to the national criminal law, with respect to Article 617 of the Comprehensive Organic Code where it is established that: "At the request of the parties, the President of the Court may order the receipt of evidence that has not been offered in a timely manner, provided that the following requirements are met: 1. Whoever requests, justifies not knowing their existence but until that moment. 2. That the requested test is relevant to the process ", thus demonstrating the violation of procedural principles of Contradiction and Equality of Opportunities and the right to Defense, as a fundamental guarantee of Due Process, as it does not have the necessary time and the necessary means for its preparation. In the course of the investigation, we will address that the unsolicited Test is opportunely constituted as a new, last-minute and even surprising means of proof, since its reception is made once the procedural stage of the Evaluation and Preparatory Hearing has been precluded of Judgment that precisely is based on announcing the totality of the tests that will be practiced in Judgment as well as to formulate requests, objections and expositions that they deem relevant referring to the evidence presented by the procedural subjects involved. 5 For the fulfillment of the proposed objectives, I proceeded to carry out the theoretical, legal and doctrinal compilation, without neglecting the comparative legislation, and the field investigation in relation to the acceptance of unsolicited evidence in a timely manner against principles procedural and due process guarantees established in the Supreme Law. Likewise, the application of methods and techniques such as the survey and the interview that were addressed to legal professionals allowed me to obtain concrete criteria, with clear and precise foundations to propose reforms necessary to solve this problem. The aspects described above are studied in this paper, which concludes with the proposal of a legal proposal according to the current legal reality, aimed at the respect of constitutional mandates, with the right to defense being one of the fundamental pillars of Due Process for the protection of people in relation to the criminal process, guaranteeing the effective protection of their rights and reaching a just resolution where the punitive or sanctioning power of the State observes the respect of principles, rights and constitutional guarantees.